Epidemiologic studies of chagas' disease in the urban zone of Teresina. State of Piauí, northeastern Brazil - Dalva N. da C. Bento; Ana Z. C. L Branco; Marise R. Freitas; Artur da S. Pinto (Sociedade Brasileira de Medicina Tropical (SBMT), 1984)
The triatomine species Rhodnius nasutus and Triatoma pseudomaculata were captured on palm trees Orbignya martiana "babaçu ", in the urban zone of Teresina. This kind of palm tree is largely distributed in Piauí State. The predominant species was R. nasutus; the young in stars predominated. The infestation index of palm trees and the infection index of triatomines by flagellates were 96.0 ana 29.1%, respectively. Marsupiais, bats and a rodent were captured in palm trees. The flagellates found in both triatomines ana marsupiais were morphologically and biologically indistinguishable from Trypanosoma cruzi. Forty seven percent (481/1,025) of triatomines were found concentrated in six palm trees where marsupiais circulated. Of the total of 1,025 triatomines 230 (22%) were infected by flagellates and 53.0% (123/230) of these infected triatomines were present in the same six palm trees. No evidence of triatomine domiciliation or human transmission was observed in the houses in the vicinity of palm trees. The results suggest that marsupiais play an important role in the life-cycle of T. cruzi in this region. The natural focus of Chagas' disease, demonstrated in the present study could represent a potential epidemiological threat. As espécies de triatomíneos Rhodnius nasutus e Triatoma pseudomaculata foram capturados em palmeiras Orbignya martiana "babaçu", situadas na zona urbana de Teresina. Este tipo de palmeira é largamente distribuída no Estado do Piauí. R. nasutus foi a espécie predominante. O índice de infestação das palmeiras e o índice de infecção dos triatomíneos por flagelados foram 96.0 e 29.1%, respectivamente. O estádio de ninfa predominou entre os triatomíneos capturados. Em algumas palmeiras, foram capturados marsupiais, morcegos e um roedor. Os flagelados encontrados tanto nos triatomíneos como nos marsupiais eram morfologicamente e biologicamente indistinguíveis do Trypanosoma cruzi Quarenta e sete porcento (481/1.025) foram encontrados em seis palmeiras onde marsupiais circulavam. De um total de 1.025 ...